The Potential of Scientific Knowledge of Jamu Gendong Production as Science Learning Enrichment Source - Vivi Widya Puspita Sari; Suciati Suciati; Meida Wulan Sari (Universitas Pancasakti Tegal, 2026)
The imbalance between the demands of 21st-century globalization and students’ higher-order thinking skills, along with the limited availability of learning media integrating local wisdom, has caused science learning to be less contextual and meaningful. This research aimed to identify scientific knowledge embedded in the traditional production process of jamu gendong as a form of local wisdom. The study employed a qualitative method using an ethnographic approach, involving five jamu gendong producers as primary respondents and six science teachers as informants. Data were collected through participant observation, in-depth interviews, and documentation, and were analyzed using interactive analysis techniques. The findings revealed that the jamu gendong production process contained scientific concepts related to biology, physics, and chemistry. These results indicated that reconstructed local knowledge could function as a contextual science learning resource that supported students’ understanding of scientific concepts, fostered higher-order thinking skills, and strengthened cultural appreciation.